The Study of Javanese Politeness Strategy Used by Warung Community at Magetan - Liliana Putri Kumalasari; Rosita Ambarwati; Theresia Budi Sucihati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Politeness in speaking is an important point that must be considered in communication. Someone must speak politely so that the message conveyed can be received properly. The researcher uses qualitative method. The primary data in this research has 99 utterances. Data collection techniques are observation, documentation, and interview. Data analysis uses Miles & Huberman‘s theory (1994) namely data reduction, data display, and conclusion. This study aims to find the politeness strategy of the Javanese in the Warung community at Magetan. The object research in this study is the seller and the buyer conversation in warung. The politeness strategy consists of 4 maxims namely, kurmat, andhap asor, tepa selira, and empan papan. The result of this study from 99 utterances, the researcher gets 56 utterances to analyze in politeness strategy. It can be divided into 38 utterances (67,8%) of empan papan maxim and 18 utterances (32,8%) of kurmat maxim.